The "Philosophy Steamer" as Cognitive Category and Historical Collective Individuality. - Mehlich, Julia B. (Russian Studies in Philosophy, 2022)
This article discusses development of the content of the concept "Philosophy Steamer," which refers to the 1922 expulsion from Russia of a group of intelligentsia who sharply criticized the authorities. The author shows that the group of exiled philosophers was united both by their previous philosophical and social activity and by their joint activity as émigrés. She analyzes the concepts of "historical collective individuality," "collective person," and "communal person" introduced by Lev P. Karsavin in order to determine the holistic nature of this exiled social group and its characteristic self-consciousness, behavior, aspirations, and feelings (moods). Examining the event known as the "Philosophy Steamer" through the concepts listed above allows the author to cognize the historical, social, and cultural reality more broadly and productively. The article demonstrates that the concept of a collective person can also be applied to other social groups, thereby extending the methodology of human-studies cognition beyond the study of facts and statistical data.